IMPLEMENTASI KRIPTOGRAFI VIGENERE CIPHER DENGAN PHP - Muhammad Dedi Irawan (Universitas Asahan, 2017)
Abstract - This research was conducted to create a cryptographic implementation of vigenere ciphers. This system is designed by analyzing the descriptive method, and the comparative method. After analysis, modeling is done with UML (Unified Modeling Language) and the design of vigenere cipher cryptography system with text encryption and decryption can be programmed using PHP software. The results of this study are an implementation of the vigenere cipher cryptographic system with PHP. Keywords - Cryptography, Vigenere Cipher, Encryption - Decryption, Text, PHP.